Experimental Investigation on the Energy Absorption Capability of Foam-filled Nomex Honeycomb Structure - Wan Abdul Hamid, Wan Luqman Hakim; Aminanda, Yulfian; Shaik Dawood, Mohd. Sultan Ibrahim (Trans Tech Publications Ltd., Switzerland, 2013)
The effect of low density filler material comprising polyurethane foam on the axial crushing resistance of Nomex honeycomb under quasi-static compression conditions was analyzed. Honeycombs with two different densities, two different heights and similar cell size, along with five different densities of polyurethane foams were used in the research. A total of 14 unfilled Nomex honeycombs, 15 polyurethane foams, and 39 foam-filled Nomex honeycombs were subjected to quasi-static compression loading. The crushing load and capability of foam-filled Nomex honeycomb structure in absorbing the energy were found to increase significantly since the cell walls of honeycomb were strengthened by the foam filler; the walls did not buckle at the very beginning of compression loading. The failure mechanism of the foam-filled honeycomb was analyzed and compared with the unfilled honeycomb.